Synthesis and Preliminary Kinetic Study of 5-fluorouracil Derivatives for Targeting Colon Tumor - Mohammed, Mohammed H.; Rahi, Firas Aziz; Naji, Hasanain Amer (JOURNAL OF ADVANCES IN CHEMISTRY, 2011)
5-Fluorouracil (5-FU) is used widely as an anticancer drug to treat solid cancers, such as colon, breast, rectal, and pancreatic cancers; although it’s clinical application is greatly limited by its short plasma half-life, poor tumor affinity, myelosuppression, and gastrointestinal toxicity. To tackle these problems, numerous modifications of the 5- Fu structure have been performed.Thus, 5-Fu as possible colon specific prodrugs were synthesized in which 5-Fu is attached to amino acids (alanine & phenylalanine) using succinate group as a spacer via amide or ester bond. An approach to improve the properties of 5-fluorouracil is the chemical transformation into bioreversible derivatives (prodrugs) which are converted to the parent drug by enzymatic and / or chemical hydrolysis. The synthesis of the target compounds were accomplished following multistep reaction procedures, the chemical reaction followed up and the purity of the products were checked by TLC. The structures of the final compounds were confirmed by their melting points, infrared spectroscopy and 1H-NMR spectra. The hydrolysis of compounds III, IV, V, and VI in aqueous buffer solutions of pH 1.2 and pH 7.4 were studied. Compounds III, IV, V and VI had enough stability at pH 1.2 (t = 429.874min, t =429.874min, t=334.336min and t =376.139min respectively) and at pH 7.4 (t=601.823min, t=601.823min, t=429.874min and t=501.519min respectively); expecting that hydrolysis of these compounds by microbial enzymes in the colon will deliver 5-fluorouracil spontaneously.